Antimicrobial consumption in food animals in Fiji: Analysis of the 2017 to 2021 import data - Magiri, Royford; Dissanayake, Chaminda; Okello, Walter (Frontiers in Antibiotics, 2022)
Introduction Globally, the demand for animal protein for human consumption has beenQ7 Q6increasing at a faster rate in the last 5 to 10 decades resulting in increasedantimicrobial consumption in food producing animals. Antimicrobials arefrequently used as part of modern methods of animal production, which mayput more pressure on evolution of antibiotic resistant bacteria. Despite theserious negative effects on animal and human health that could result fromusing antibiotics, there are no assessment of antimicrobials consumed by thelivestock sector in Fiji as well as other Pacific Island Countries. The objective ofthis study was to quantify antimicrobials imported for consumption in foodanimals into Fiji from 2017 to 2021. Methods Data on imported antimicrobials, whichwere finished products, was obtained from Biosecurity Authority Fiji (BAF).Imported antimicrobials were then analyzed by antimicrobial class, andimportance to veterinary and human medicine. Results An average of 92.86 kg peryear (sd = 64.12) of antimicrobials as a net weight was imported into Fiji in the2017-2021 study period. The mean amount of imported active antimicrobialingredients after adjusting for animal biomass was 0.86 mg/kg (sd = 0.59). Fromthe total antimicrobial imports during the years 2017 to 2021, penicillins(69.72%) and tetracycline (15.95%) were the most imported antimicrobialclasses. For animal health 96.48% of the antimicrobial imports wereveterinary critically important antimicrobials. For human healthfluroquinolones, macrolides, aminoglycosides, and penicillins were theimported critically important antimicrobials. Discussion The study concluded that use ofantimicrobials in food producing animals is low but monitoring of antimicrobialconsumption and antimicrobial resistance was critical in Fiji due to overrelianceon critically important antimicrobials.